(untitled) (Medical Forum Monthly, 2020)
Objective: The objective of the present study was to determine the diagnostic accuracy of CRP for evaluation of spontaneous bacterial peritonitis in patients keeping ascetic fluid neutrophilic count more than 250/mm3 as a gold standard. Study Design: Cross Sectional Validation study. Place and Duration of Study: This study was conducted at the Department of Gastroenterology and Medicine Poonch Medical College Rawalakot from October 2019 to January 2020. Materials and Methods: All diagnosed cases of Chronic Liver Disease having ascites admitted in gastroenterology ward or presenting in the emergency department from 18 years and above, both male and female were included in the study by consecutive sampling were included in the study. A diagnosis of spontaneous bacterial peritonitis was made and documented if > 250 /mm3 neutrophils were found in ascitic fluid. A serum sample was drawn for CRP and the results were reported in mg/L. Serum CRP level of ≥ 29.5mg/L was considered as significant. Results: Total 210 patients were included in the study. There were 60.95% (n=128) male and 39.04% (n=82) female patients with the mean age of 43.36+13.68 years (range 19-78 years). Spontaneous bacterial peritonitis was diagnosed in 28.09% (n=59) patients, CRP levels was greater than 29.5mg/L in 29.52% (n=62) patients. Sensitivity was 83.05% and specificity was 91.39 %. Negative Predictive Value was 93.24% and Diagnostic Accuracy was 89.04%. Conclusion: CRP is reliable serum marker for rapid diagnosis of spontaneous bacterial peritonitis in patients admitted due to complications of cirrhosis.